Concussion management in combat sports: consensus statement from the Association of Ringside Physicians. Issue 6 (26th July 2018) - Neidecker, John; Sethi, Nitin K; Taylor, Randolph; Monsell, Raymond; Muzzi, Don; Spizler, Bruce; Lovelace, Larry; Ayoub, Edmund; Weinstein, Rick; Estwanik, Joseph; Reyes, Patricio; Cantu, Robert C; et al.
Abstract : Various organisations and experts have published numerous statements and recommendations regarding different aspects of sports-related concussion including definition, presentation, treatment, management and return to play guidelines. 1–7 To date, there have been no written consensus statements specific for combat sports regarding management of combatants who have suffered a concussion or for return to competition after a concussion. In combat sports, head contact is an objective of the sport itself. Accordingly, management and treatment of concussion in combat sports should, and must, be more stringent than for non-combat sports counterparts. The Association of Ringside Physicians (an international, non-profit organisation dedicated to the health and safety of the combat sports athlete) sets forth this consensus statement to establish management guidelines that ringside physicians, fighters, referees, trainers, promoters, sanctioning bodies and other healthcare professionals can use in the ringside setting. We also provide guidelines for the return of a combat sports athlete to competition after sustaining a concussion. This consensus statement does not address the management of moderate to severe forms of traumatic brain injury, such as intracranial bleeds, nor does it address the return to competition for combat sports athletes who have suffered such an injury. These more severe forms of brain injuries are beyond the scope of this statement. This consensus statement does not address neuroimaging guidelines in combat sports.